2017
DOI: 10.1080/14427591.2016.1269240
|View full text |Cite
|
Sign up to set email alerts
|

Occupational adaptation and identity reconstruction: A grounded theory synthesis of qualitative studies exploring adults’ experiences of adjustment to chronic disease, major illness or injury

Abstract: Occupational adaptation and identity reconstruction-A grounded theory synthesis of qualitative studies exploring adults' experiences of adjustment to chronic disease, major illness or injury

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 64 publications
5
44
0
Order By: Relevance
“…Motivation, another theme in the study, was shown to be dynamic, complex and multifactorial. Consistent with other studies (Ellis-Hill et al, 2009;Luker et al, 2015;Walder & Molineux, 2017a) participants in this study identified that periods of low motivation were often underpinned by fatigue or lack of progress. Occupational therapists must remain cognisant of individual motivational factors and adjust services in line with client needs.…”
Section: Discussionsupporting
confidence: 90%
“…Motivation, another theme in the study, was shown to be dynamic, complex and multifactorial. Consistent with other studies (Ellis-Hill et al, 2009;Luker et al, 2015;Walder & Molineux, 2017a) participants in this study identified that periods of low motivation were often underpinned by fatigue or lack of progress. Occupational therapists must remain cognisant of individual motivational factors and adjust services in line with client needs.…”
Section: Discussionsupporting
confidence: 90%
“…The focus of occupational therapy is to help individuals achieve health, well-being, and participation in life through engagement in occupations. A significant health event, such as a stroke, can cause a sudden and significant change in occupational ability [1]. Thus, the event of having a stroke carries the potential risk of affecting the ability to engage in occupations.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional support promotes positive interactions between the adolescent and significant others in their environment. This is important given the impact of the TBI on the adolescent's emotional functions that may affect their interpersonal interactions and relationships, specifically with those whom they rely on for support [14, 31, 41, 42]. As primary caregivers in this study highlighted that TBI also has an impact on the family unit, it is imperative that emotional support should be provided to the family of the adolescent with TBI.…”
Section: Discussionmentioning
confidence: 96%
“…These changes often impacted negatively on their self-esteem, motivation, and competence in their day to day functioning. This in turn negatively impacted on their sense of belief in self and on their ability to transition to various life situations post TBI including that of school [31]. As a facilitator , the occupational therapist may cultivate the adolescent's belief in self through facilitating the adolescent's skill development and experiences of mastery through enabling the adolescent to identify and employ remediative and compensatory strategies that allow for the engagement in academic, nonacademic, and extracurricular school-related activities.…”
Section: Discussionmentioning
confidence: 99%